A New High Hydrostatic Pressure Process to Assure the Microbial Safety of Human Milk While Preserving the Biological Activity of Its Main Components - Demazeau, Gérard; Plumecocq, Adrien; Lehours, Philippe; Martin, Patrice; Couëdelo, Leslie; Billeaud, Claude (Frontiers in Public Health, 2018)
Background: The main process used to pasteurize human milk is the low-temperature, long-time Holder method. More recently, the high-temperature, short-time method has been investigated. Both processes lead to the appropriate inactivation of vegetative bacterial forms but are ineffective against bacterial spores. Research Aims/Questions: We aimed to accomplish two main objectives: inactivation of all pathogens, including spores; and preservation of the activity of milk components. Design/Methods: Recently, a novel high-hydrostatic pressure process has been developed by HPBioTECH. Using the same raw human milk samples, we compared the effects of this method with those of the Holder method on vegetative and spore forms of pathogens and on bioactive components (lipase activity, immunoproteins). Results: Two main microbial strains were selected: Staphylococcus aureus (as a reference for vegetative forms) and Bacillus cereus (as a reference for spores). Use of the high-hydrostatic pressure process led to microbial decontamination of 6 log for both S. aureus and B. cereus. Additionally, the bioactivity of the main components of human milk was preserved, with activities of lipase, α-lactalbumin, casein, lysozyme, lactoferrin, and sIgA of ~80, 96–99, 98–100, 95–100, 93–97, and 63–64%, respectively. Conclusions: Use of this novel high-hydrostatic pressure process to generate microbiologically safe human milk may provide important benefits for preterm infants, including improved assimilation of human milk (leading increased weight gain) and improved resistance to infections. Because 10% of all human milk collected is contaminated by B. cereus, use of this method will also prevent waste.